Boosting Resilience Attentional Bias in Previously Bullied University Students with Low Post-Traumatic Growth: A Transcranial Direct Current Stimulation Study - Yennifer Ravelo; Rosaura Gonzalez-Mendez; Olga M. Alegre de la Rosa; Hipólito Marrero (Brain Sciences)
Background/Objectives: Post-traumatic growth (PTG) has the potential to draw positive consequences from trauma. Hence, there is interest in finding ways to promote PTG. Research has identified an attentional bias towards positive resilience-related words (e.g., “persistence”, “purpose”) in university students who report high PTG after experiencing adversities. Although people can respond to these experiences by showing low PTG, this bias seems to help with their struggle by making purposeful contents more accessible. Therefore, boosting attentional bias towards positive resilience-related words could help people with low PTG. Methods: In this study, the participants were thirty-six university students who had experienced bullying before entering university. Using a Stroop emotional task, they identified the color of resilience and neutral words, either positive or negative, before and after being submitted to transcranial direct current stimulation. Stimulation was targeted at the right temporal area involved in intentionality processing. Results: In the anodal condition, the results support a stimulation effect on the resilience attentional bias that could benefit participants with low PTG. A significant moderation of approach motivation for this effect was also found. Specifically, only when participants had medium or high approach motivation did stimulation boost the attentional bias in students with low PTG. Conclusions: These results support that tDCS stimulation in this brain area is effective in enhancing resilience attentional bias in low-PTG students. However, for this effect to occur it is necessary to have approach motivation, which is motivation related to goals.